Problematics Legality Building of Mosque Without Establishing Building Permit in Aceh - Fuadi Fuadi; Muhammad Natsir; Meta Suriyani (Syiah Kuala Law Journal, 2021)
This study discusses the condition of a large portion of mosque buildings in Aceh that do not have a Building Construction Permit (IMB) by statutory regulations. For the legalization and legal certainty of mosque building in Aceh, it is necessary to find a solution, considering that mosques are places of worship for Muslims that have multi-functions and are very sensitive in nature. This research is a descriptive qualitative study on people's behavior, a situation, thought systems, and events related to the permit of mosque buildings in Aceh. Using public policy theory in providing legal protection to people who have built mosques independently. The results showed that mosque buildings in Aceh in general did not have an IMB because the administrative requirements were not fulfilled in the form of a waqf certificate for asceticism of mosque buildings. Efforts to ensure legal certainty for local governments need to issue a special bleaching program policy for mosque building permits in Aceh.